DESAIN DAN ANALISIS KEHANDALAN DRILLING PRODUCTION PLATFORM TIPE JACKET DELAPAN KAKI DI PERAIRAN LAUT NATUNA - Junior Yahya Simbolon - NIM 15513042 , Alexander
Design offshore structure involve some loads in random variable. Loads that applicate to the structure, generally conducted with WSD (Working Stress Design) and LRFD (Load and Resistance Factor Design) criterion which has different load factor application. This criterion used to ensure structure is safe as its fuction as structure in predetermined period. In this final assignment, structure used fixed type structure (Jacket Structure) and used API RP2A LRFD design criterion. API RP2A LRFD is the code created by North America Sea condition, especially Gulf of Mexico Sea where has more extreme environtmental condition than Indonesia’s Sea. Therefore, this load factor in API RP2A LRFD criterion need to be reviewed for application Indonesia’s Sea especially Natuna Sea. In this final assignment, structure must be designed in optimum condition. To design the optimum structure, there are three analysises should conducted, there are Inplace Analysis, Seismic Analysis, and Fatigue Analysis. These analysises have each design criterion. In this final assignment, reliability parameter determined with Unity Check (UC) member performancy for predetermined member. That member determined by result of Inplace Analysis. Reliability Analysis conduct with Monte Carlo method. Result of Reliability Analysis is Reliability Index which represented reliability of structure.